2019
DOI: 10.1002/jbio.201800397
|View full text |Cite
|
Sign up to set email alerts
|

In vivo testing of a bioresorbable phosphate‐based optical fiber

Abstract: Optical fibers have recently attracted a noticeable interest for biomedical applications because they provide a minimally invasive method for in vivo sensing, imaging techniques, deep‐tissue photodynamic therapy or optogenetics. The silica optical fibers are the most commonly used because they offer excellent optical properties, and they are readily available at a reasonable price. The fused silica is a biocompatible material, but it is not bioresorbable so it does not decompose in the body and the fibers must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Predicting the in vivo degradation rate of bioPOFs based on our in vitro results is challenging though. We can nevertheless refer to [46] which reported on the lower solubility of bioresorbable optical fibers in animal body. The slower degradation was attributed to the encapsulation of the fiber in tissue that limits contact with renewed physiological fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the in vivo degradation rate of bioPOFs based on our in vitro results is challenging though. We can nevertheless refer to [46] which reported on the lower solubility of bioresorbable optical fibers in animal body. The slower degradation was attributed to the encapsulation of the fiber in tissue that limits contact with renewed physiological fluid.…”
Section: Discussionmentioning
confidence: 99%
“…After the immersion in phosphate buffer saline (PBS) for 10 days, silicon waveguide can be completely dissolved. Podrazky et al utilized phosphate glass fiber as the bioresorbable optical waveguide [73], as shown in Figure 1c. The phosphate-based optical fiber has good transparency and its solubility in water can be adjusted by changing the chemical composition to meet the requirements on the operation period.…”
Section: Optical Waveguidementioning
confidence: 99%
“…Unfortunately, these sensors are bulky in size, they often exhibit a rather poor performance in both extremes of the pH scale and they also have to be re-calibrated in a discontinuous way [ 4 ]. In recent years, substantial efforts were invested towards the development of optical fiber-based pH sensors [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%